Social Skills Of Students In The Pandemic Period - Mareta, Prima Retnaning; Musadad, Akhmad Arif; Susanto, Susanto (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The pandemic period which is increasingly protracted and it is not clear when it will end has disrupted all human activities, one of which is learning activities in school. After the physical distancing rules are implemented, student learning activities are carried out at home. This results in students experiencing a decrease in student affective skills, besides that the teacher also experiences limitations in monitoring student affective behavior. Therefore, this study aims to determine the extent to which students' social skills during the pandemic. The research subjects were students of SMA Negeri 1 Kedunggalar, Ngawi Regency, with 76 students as respondents who were randomly selected from various classes, majors, and genders. This research is a qualitative descriptive study. Data collection techniques using a questionnaire. Data analysis in this study refers to an interactive analysis model consisting of the stages of data reduction, data presentation, and data verification. From this research, the goal is to be able to see how the attitude of students' social skills during the pandemic.